The Role of Financial Influencers, Financial Content Exposure, Social Influence, Fear of Missing Out, and Self-Control in Generation Z's Investment Decision-Making in the Digital Era - Rizky Aulya; Fatchan Achyani (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the role of financial influencers, financial content exposure, social influence, fear of missing out (FOMO), and self-control in Generation Z's investment decision-making in the digital era. A quantitative associative research design was employed involving Accounting students at Universitas Muhammadiyah Surakarta from the 2022–2024 cohorts. A total of approximately 310 respondents were selected through purposive sampling from a population of 1,386 students (Sugiyono, 2023). Primary data were collected using an online questionnaire with a five-point Likert scale and analyzed using SPSS through descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression, followed by the coefficient of determination (R²), F-test, and t-test at a 5% significance level (Ghozali, 2021). The findings reveal that financial influencers and self-control have positive and significant effects on Generation Z's investment decisions. In contrast, financial content exposure, social influence, and fear of missing out (FOMO) do not significantly influence investment decisions. These results suggest that investment decisions among Generation Z are primarily driven by trusted financial sources and the ability to exercise self-control rather than by social pressure or extensive exposure to financial content.